Silicon Based Hybrid Photonic Crystal Waveguide With Defects For Directional Coupler And Ring Resonators - Bakar, Ronald (2024)
Photonic crystals (phc) have been studied for photonic integrated circuits whereby optical fibres are considered for modern wavelength division multiplexing (wdm) applications. This study focuses on a phc as candidate for miniaturization of wdm. Two-dimensional (2-d) silicon (si) rods on silicon dioxide (sio2) consisting of directional coupler (dc) and phc ring resonator (pcrr)s are designed and simulated using optifdtd by plane wave expansion (pwe) and finite difference time domain (fdtd). A gap map was obtained using pwe by setting the photonic band gap for si-on-sio2 as 0.64174 < 1/λ < 0.768518 and si-on-air as 0.657996 < 1/λ < 0.942283. The chosen wavelengths are within optical communications wavelengths of 1.31 μm < λ < 1.55 μm. Rod radius, r and lattice constant, a, are determined respectively at 94.0 nm and 0.4 μm; r/a is 0.235. A dc is built by adding line defects, decoupling 1.31 μm and 1.55 μm inputs. Three pcrrs are separately built with cavity point defects as resonator. When the rod radii is 65.8 nm, 75.2 nm, and 84.6 nm respectively, the dc demonstrated demultiplexing of 1.31 μm and 1.55 μm within range of coupling lengths 8.4 μm <